2013
DOI: 10.1038/sj.bdj.2013.222
|View full text |Cite
|
Sign up to set email alerts
|

The use of porous titanium granules for treatment of peri-implantitis lesions: preliminary clinical and radiographic results in humans

Abstract: The use of porous titanium granules might be a viable treatment option in cases of peri-implantitis lesions. Further large-scale long-term studies are warranted in order to assess the additional benefit from this treatment option compared to other available alternatives. assiduous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 8 publications
0
32
0
Order By: Relevance
“…Mechanical decontamination is performed by using the following: titanium, plastic, and teflon curettes; sonic and ultrasonic devices; the air‐powder abrasion technique; titanium brush and laser; chemical solutions; chlorhexidine digluconate, citric acid, hydrogen peroxide, and sterile saline . It was reported that in implant surface decontamination, tetracycline HCl was used as the antibiotic . These materials used for decontamination are not superior from each other.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical decontamination is performed by using the following: titanium, plastic, and teflon curettes; sonic and ultrasonic devices; the air‐powder abrasion technique; titanium brush and laser; chemical solutions; chlorhexidine digluconate, citric acid, hydrogen peroxide, and sterile saline . It was reported that in implant surface decontamination, tetracycline HCl was used as the antibiotic . These materials used for decontamination are not superior from each other.…”
Section: Introductionmentioning
confidence: 99%
“…27,43 A number of studies which did not satisfy the inclusion criteria were eliminated from those included in the present review (Table 6). [55][56][57][58][59][60][61][62][63] In group 1, MD with or without saline, at 12-month follow-up, the best outcomes were achieved by HeitzMayfield et al 37 treating 36 implants reporting a PD reduction of 2.4 mm (45% of initial PD) and Schwarz et al 36 treating 9 implants reporting a PD reduction of 2.7 mm (39% of initial PD). Both studies used MD and saline for SDC.…”
Section: Resultsmentioning
confidence: 99%
“…31 Further evaluation of this option is required. 32 The complication rate with regenerative procedures around previous peri-implantitis defects has been reported to be relatively high with infection, implant loss and membrane exposure reported in up to 88% of cases. [33][34][35] Further questions such as the susceptibility of grafted bone to further microbiological insult also requires evaluation.…”
Section: Guided Bone Regenerationmentioning
confidence: 99%